PERAN DEPARTEMEN PENGASUHAN SANTRI DALAM PENANGANAN PERILAKU BULLYING DI PONDOK PESANTREN ANNAKHIL DARUNNAJAH 6 MUKOMUKO BENGKULU - Muhammad Fikri Ghozali (Perkumpulan Dosen Program Hibah Indonesia, 2024)
This research examines the role of the student care department and handling bullying behavior. Bullying is a dangerous problem that is disturbing the world of education at age levels throughout the world. Bullying is a power gap factor that arises from physical aspects, access to social media that contains embarrassing information, popularity factors, and the desire to hurt other people. So the role of the Student Care Department is really needed to handle this. This research uses a descriptive qualitative approach method. Data collection was carried out using observation, interview and documentation techniques. Then the data analysis technique uses how to describe the data, analyze all the data and then make a conclusion. The aim of this research is to find out the role of the student care department in dealing with bullying behavior. The results of this research are that the role of the Student Care Department in handling bullying has been running effectively. However, it is not yet running optimally. The inhibiting factor is that it is less effective due to a lack of motivation within the students so they feel embarrassed and afraid to report bullying behavior and this has become a habit so it is considered normal.